Energy expenditure assessed by heart rate and doubly labeled water in young athletes - Ekelund, U.; Yngve, A.; Westerterp, K.; Sjöström, M. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: To compare total energy expenditure (TEE) estimated by the FLEX heart rate (HR) method with that measured by the doubly labeled water (DLW) technique in young speed skaters. We hypothesized that the accuracy of FLEX HR-estimated TEE would be affected by a) the definition of the FLEX HR and b) the type of training regimen. METHODS: Eight young athletes (mean age 18.2 +/- 1.3 yr) underwent measurements during two 10-d training periods: an off-season period with voluntary training (predominantly running) and a preseason period mainly focused on skating technique training. TEE was measured simultaneously by the DLW and FLEX HR methods. FLEX HR1 was defined as the mean of the HRs during all resting calibration activities and the lowest HR during exercising calibration activities. FLEX HR2 was defined as the mean of the highest HR during resting activities and the lowest HR during exercising. RESULTS: ANOVA showed that FLEX HR1 was significantly lower than FLEX HR2 (mean of both periods; 77 +/- 5 vs 84 +/- 6 beats.min-1; P = 0.004). TEE values obtained by DLW were 16.8 +/- 3.8 and 16.9 +/- 2.9 MJ.d-1 in the two periods, respectively. TEE values calculated from FLEX HR1 were 17.8 +/- 3.6 and 17.4 +/- 2.6 MJ.d-1, and those from FLEX HR2 17.1 +/- 3.1 and 17.0 +/- 2.7 MJ.d-1, respectively. No significant period (P = 0.83) or method (P = 0.44) effect on TEE was observed. CONCLUSION: FLEX HR-estimated TEE was not affected by the definition of the FLEX HR or by the type of training regimen as compared with TEE measured by the DLW method in young athletes.